Aromaticity/Antiaromaticity Effect on Activity of Transition Metal Macrocyclic Complexes towards Electrocatalytic Oxygen Reduction - Ni, Youxuan; Lu, Yong; Zhang, Kai; Chen, Jun (ChemSusChem, 2021)
The effect of the coordination sphere around metal centers on the oxygen reduction reaction (ORR) activity of transition metal macrocyclic complexes is still unclear. Here, the aromaticity/antiaromaticity effect of macrocycles on ORR activity was investigated based on TM norcorrole (TM=Mn, Fe, Co, Ni), TM porphycene, and TM porphyrin by first‐principle calculations. It was found that the complexes with weaker aromatic macrocycles exhibited a stronger adsorption strength while the complexes with antiaromatic macrocycles showed further enhanced adsorption strengths. Further investigations indicated that the variation in the adsorption strengths of catalysts was attributed to the different redox activities of macrocycles with different aromaticities. Such difference in redox activities of macrocycles was reflected in the activities of metal centers via d–π conjugation, which acted as a bridge between π‐electrons on macrocycles and active d‐electrons on metal centers. This work deepens the understanding of the role of macrocycles in oxygen electroreduction. (Anti)aromaticity: The aromaticity/antiaromaticity effect of macrocycles on ORR activity of transition metal macrocyclic complexes is unveiled by first‐principle calculations. Macrocycles with weak aromaticity have an improvement in adsorption strength for intermediates on metal centers while antiaromatic macrocycles can greatly strengthen the activity of metal centers.